UNSUR BARU TINDAK PIDANA PERJUDIAN ONLINE BERDASARKAN UNDANG-UNDANG NARKOTIKA (STUDI PUTUSAN NOMOR 579/PID.B/2023/PN SBY) - Alwi, Ahmad Junaidi; Maria Novita Apriyani (HUKMY : Jurnal Hukum, 2024)
This article analyzes the development of gambling with a new approach to its implementation. Referring to the case at the Surabaya District Court Number 579/Pid.B/2022/PN Sby, the author presents a new perspective regarding elements that have not been accommodated in the Criminal Code and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, which regulate criminal acts of gambling based on Law Number 35 of 2009 concerning Narcotics. Charges based on Article 303 paragraph (1) of the Criminal Code and Article 27 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions are basically sufficient to ensnare online gambling, but are less appropriate if The event that is accused of being a criminal act of gambling is actually a buying and selling transaction. Law enforcement in Indonesia is based on the principle of legality. The purpose of writing this article is to provide readers with a new perspective regarding the factors that can be categorized as criminal acts of gambling. This article reveals findings regarding elements of gambling that have not been regulated in previous legislation. The research method used in writing this article is a normative approach, which involves research into legal sources and literature review.